How does the Theory of Planned Behavior Mediate The Relationship Between Financial Literacy And Impulse Buying on Live Selling Platforms? - Amalia, Putri; Firmialy, Sita Deliyana (Department of Management, Faculty of Economics and Business, Brawijaya University, 2024)
Live-streaming platforms allow for direct communication between merchants and consumers, serving as a promotional platform. Using the Theory of Planned Behavior as a mediating variable, this study seeks to determine how financial literacy affects impulse buying among Indonesian consumers from the Millennial Generation and Generation Z. This study employed a quantitative research methodology and administered questionnaires to 100 individuals. The questionnaire responses were analyzed using the SEM-PLS analysis method with the Smart PLS 4.0 software. The findings of this study indicate that financial literacy has a notable and meaningful impact on Attitude and perceived behavioral control. Additionally, Attitude positively and significantly influences impulse buying behavior, while subjective norms shape this behavior. Moreover, perceived behavioral control positively and significantly influences impulse buying behavior. Furthermore, financial literacy indirectly affects impulse buying behavior through Attitude and perceived behavioral control as mediating variables.